RELATIVE IMPORTANCE AND INTERACTION OF ROASTING VARIABLES IN COFFEE ROASTING PROCESS - Garcia, Cinthia da Conceição; Pereira Netto, Annibal Duarte; da Silva, Michelle Costa; Catão, Alexandre Alves; de Souza, Iasmim Amorim; Farias, Larissa Silva; Emerich de Paula, Thiago Nunes; Emerick de Paula, Mateus Nunes; dos Reis, Sandro Coutinho; da Silva Junior, Ademário Iris (Coffee Science - ISSN 1984-3909, 2018)
This work describes a study in which levels of variables that may control the coffee roasting process were set in an experimental matrix that aimed at measuring their relative importance and the interaction between variables. Each control variable was set in two levels and the combination of these levels elicited 32 different roasting procedures. The physical responses were determined for a specific roaster. Experimental planning allowed the determination of the relative influence of each control variable in each response variable for this roaster. This led to a primary quantification of the major factors that contribute to the roasting process and the relative importance of roast parameters that influence the quality of the coffee beverage. Moreover, these results indicated what interactions could occur between these parameters. The characterization of the relative influence of control variables is a first approach to model the roaster response and the coffee quality that each roasting can achieve.